Comparación de ácido hialurónico y miel de abeja en la cicatrización y en el desarrollo de bacterias en la mucosa de cobayos: estudio in vivo. - Artieda Barragán, Cristhian David (2024)
Objective: To compare – in vivo- the topical application of hyaluronic acid and honey in the healing and development of bacteria in the mucosa of guinea pigs. Material and methods: In vivo study conducted on a sample of 30 guinea pigs, divided into three groups, all under identical conditions (location, feeding, temperature). For five consecutive days, both in the morning and in the evening, the following treatments were topically applied: hyaluronic acid in Group A, bee honey in Group B, while no substances were applied in Group C (GC). This was carried out using a hypodermic syringe. Prior to sedation, a circular incision of 4 mm was made in the mucosa of guinea pigs in the infero-lateral left region of the incisors. Characteristics such as bleeding, edema, erythema (on days 4, 6, and 8), scar tissue, presence of suppuration (day 8), and bacterial culture (to measure colony-forming units, CFU) were identified at the wound site. Results: The group that was applied hyaluronic acid during the evolution of the wound presented a decrease in bleeding, edema and erythema, in addition, the formation of 4 mm scar tissue on the sixth day was 60.00% (n=6), there was 80.00% (n=8) epithelial union on the eighth day and demonstrated a lower amount of CFU in the analysis ranges. Conclusions: Topical application of hyaluronic acid contributes to the formation of scar tissue, wound closure, and a decrease in bacterial formation.